Fear of falling and its related factors in older adults following a fall in Kashan, Iran (2023–2024) - Fatemeh Sadat Izadi-Avanji; Azade Safa; Masoumeh Abedzadeh-Kalahroudi; Negin Shaterian (BMC Geriatrics)
Abstract Background Falling is a significant challenge in old age, often leading to isolation, self-imposed limitation, reduced movement, and muscle strength. This study aimed to explore the fear of falling and its related factors in older adults following a fall in Kashan, Iran. Methods This cross-sectional study followed 200 older adults who visited medical centers in Kashan from July 2023 to May 2024. Continuous sampling was carried out. Data collection involved a background information questionnaire, the shortened version of the falls efficacy scale-international in older adults, the independence scale of activities of daily living, and the short-form state-trait anxiety inventory. Data were gathered before, one month, and three months after the fall. Data analysis utilized SPSS-24, including t-test, ANOVA, Pearson’s correlation coefficient, and repeated measures analysis of variance. Results Participants had a mean age of 71.34 ± 8.36 years (ranging from 65 to 96 years). There was a significant increase in fear of falling scores one month and three months after the fall (P < 0.001). Multiple linear regression revealed that factors such as illiteracy, old age, and previous falls were predictors of fear of falling before the fall (P < 0.05). One month after the fall, predictors included illiteracy, hip fracture, and high anxiety scores (P < 0.05). Three months after the fall, predictors encompassed illiteracy, hip fracture, high anxiety score, and internal fixator placement as a treatment intervention (P < 0.05), explaining 15% of the variance in fear of falling. Conclusions Identifying predictive factors for fear of falling can assist health policymakers in developing a holistic care plan to enhance the quality of life for older adults post-fall. It is essential to screen for fear of falling levels, particularly after trauma, offer educational counseling services, particularly in mental health, after discharge, and prepare training programs related to fall prevention.